PKM PENANAMAN BIBIT KACANG PANJANG DI DESA TANI BHAKTI SAMBOJA BARAT KUTAI KARTANEGARA - Dwi Taufik Rohman; Cinta Amalia; Febi Ghalsananda; Ghea Asya Hermanita; Intan Cahyani Sari; Rafli Ocis Alexsandro Latupeirissa (LPPM Universitas Bina Bangsa, 2023)
Tani Bhakti Village, West Samboja District, Kutai Kartanegara Regency, is a village with a large number of people working as farmers and ranchers. Therefore, there are various agriculture and plantations in Bhakti Tani Village. In accordance with the theme of Balikpapan University's Real Work Lecture XIII, which is